Does the sixth wave of COVID‐19 break in Okinawa? - Masaki Tomochi; Mitsuo Kono (Journal of General and Family Medicine, 2022)
Abstract Background We aimed to forecast possible situations of the COVID‐19 spreading for Okinawa Prefecture in Japan. Methods The VSIIR model is proposed to extend the SIIR model to include vaccine effects where the parameter v denotes the vaccination rate and is treated as a control parameter on which possible situations for Okinawa would depend. Results It is shown that the infection ends without spreading if v>d1+d2 is satisfied where 1/di refers to the antibody duration, i=1 for infection and i=2 for vaccination, respectively. Conclusion It is important to set a vaccination policy that can save lives and maintain daily life at the same time.